The effect of fosfomycin Overdoses in kidney tissue of broiler chicken (Journal of Hama University, 2022)
The study was conducted to examine the kidneys pathological changes resulting from the administration of excessive doses of fosfomycin in 30 day old broiler chicken. The birds were divided into six groups, one of them was the control group. The experimental groups were given a single dose of fosfomycin orally daily, for 5 days, as either therapeutic (40 mg/kg), doubled (80 mg/kg) or supra-therapeutic (160-320-640 mg/kg).Three birds from each group were slaughtered  on day three (after the third dose), day six (after 24 hours from the last dose),and day nine(after withdrawing the drug from the tissues.)  of the experiment. The macroscopic changes were studied in the kidney  ,then took samples  from it , and prepared by the use of a paraffin insertion. These samples  were pigmented by the pigment of Hematoxylin and Eiosine after that the microscopic study was conducted, and the results  were recorded.The results of the study showed that there was change in the kidney tissues represented by the macroscopic hypertrophy  and  textural changes that looked like cloudy degeneration of   tubules epithelium microscopically. These changes were obvious in the third group that received the double dose(80 mg/kg). These changes become more intense as the drug dose increases. The changes were associated with necrosis in tubular  epithelium and some glomeruli in the first and second stages of the experiment . On the other hand, regeneration and restoration of kidney tissues were observed at the third stage of the experiment;( day nine) And that is after withdrawing the drug from the tissues.As a result, it is suggested to be careful not to use double doses, and if it necessary to use them in emergency cases, it is better to give diuretics to minimize the negative effects on kidneys tissues. It is also recommended not use superdose of the drug since it has functional disorder on kidney tissues.